2023
DOI: 10.1111/jvim.16843
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic functional urinary outflow tract obstruction in dogs, a retrospective case series (2010‐2021): 31 cases

Kathrina Mathews,
Christine Toedebusch,
Carrie Palm
et al.

Abstract: BackgroundIdiopathic functional urinary outflow tract obstruction (iFUOTO) is an uncommon but life‐limiting disease whose etiology and clinical course of disease remain poorly understood.ObjectiveCharacterize signalment, clinical signs, clinicopathologic findings, treatments, and propose a standardized response score for dogs with iFUOTO.AnimalsThirty‐one client‐owned dogs diagnosed with iFUOTO.MethodsRetrospective case series. Medical records from 2010 to 2021 were reviewed and findings recorded. Dogs were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In a retrospective study, bacteriuria was observed in several dogs with FOO but none of the dogs had resolution of their stranguria after appropriate antimicrobial treatment. 131 Antimicrobials could be considered at the initial presentation if bacteriuria is noted and suspected to be contributing to clinical signs, and the clinician should monitor for clinical improvement of the voiding disorder. If no improvement is observed, long‐term antimicrobials likely is not warranted.…”
Section: Treatmentmentioning
confidence: 99%
“…In a retrospective study, bacteriuria was observed in several dogs with FOO but none of the dogs had resolution of their stranguria after appropriate antimicrobial treatment. 131 Antimicrobials could be considered at the initial presentation if bacteriuria is noted and suspected to be contributing to clinical signs, and the clinician should monitor for clinical improvement of the voiding disorder. If no improvement is observed, long‐term antimicrobials likely is not warranted.…”
Section: Treatmentmentioning
confidence: 99%